(3OjfGejcjI JOQjS GdJQHjI GdQjGVjIs - (3YHO GdcQje eMehO YHO GdMdjes ((3GdbGgQIs (3eQcR GdcJGH ddfTQs, 2003)
(3jMJhj Ydi GdeJZjQGJ GdCcKQ aYGdjI aj JOQjS GdJQHjI GdQjGVjI HUhQI LjOI efgG eG jNU cGajGJ GdCOGA ddeYde hefgG eG jNU GdJdGejP hgh eSJbHd ddJOQjS h efgG eG jJUd HGdEOGQI GdeOQSjI h CSGdjH JfXjegG ddMjGI GdjhejI heG jJUd HHjFJg GdJOQjSjI heOi CgejJgG dGSJjYGH h eOi caGjJgG h CgdjJgG dOYe YedjGJ GdJOQjS (B.s